Sobre um caso de odontoma mole de transição em bovino - Rangel, N M; Machado, A V; Wilwerth, L M (Revista Ceres, 1942)
The A A. report a case of tumor of the lower jaw in a Zebu heifer, 20 months old, observed at Viçosa, State of Minas Gerais, Brazil. The tumor was localized at the region of the second and third left molar extending as far as the angle and ascending branch of the jaw. Its greatest dimensions were 23x18x14 cm. The second and third molar were absent. The cut section was solid, white and bleeding. Except for the antero-superior lace, open in the oral cavity, most of the tumor was wrapped in a fibrous capsule and, outside this, by a thin bony plate of jawbone. Microcospically the tumor was seen to consist of large strands of squamous proliferating epithelium, in various stages of differentiation of enamelled organs, and very abundant connective stroma, predominantly mucous. Around some of the enamelled organs there was production of enamelled and thin cementlike uncal- cified osteoid tissue. The A A. summarize the incidence ol such tumors, showing its rarity. Alter summarizing the different proposed classifications of dental tumors, the A A. classify this case as soft odontoma of transition between adamantinoma and multidentigerous proliferating odontoma.